Mathematical Models, Methods and Applications - Siddiqi, Abul Hasan; Manchanda, Pammy; Bhardwaj, Rashmi (Industrial and Applied Mathematics, 2015)
The present volume contains invited talks of 11th biennial conference on "Emerging Mathematical Methods, Models and Algorithms for Science and Technology". The main message of the book is that mathematics has a great potential to analyse and understand the challenging problems of nanotechnology, biotechnology, medical science, oil industry and financial technology. The book highlights all the features and main theme discussed in the conference. All contributing authors are eminent academicians, scientists, researchers and scholars in their respective fields, hailing from around the world.